Marco conceptual para el estudio de las prácticas de evaluación en una institución educativa: desde la teoría del EOS - Aparicio Pereda, Ana Sofía (2013)
This is a conceptual framework for the diagnostic study of the role of evaluation practices in the learning process in educational institutions. The framework is based on concepts given by the Onto-Semiotic Approach to mathematical knowledge and instruction (OSA), which have been adapted to this context.